Development of Halal Food MSMEs in Purwokerto: An Analysis of Challenges and Opportunities through a Qualitative Approach - Hani, Faskhatul Nur (CV. Tripe Konsultan, 2025)
This study was conducted to analyze in-depth the development of Micro, Small, and Medium Enterprises (MSMEs) in the halal food sector in Purwokerto, Central Java. This location was chosen strategically, considering that Purwokerto, as an educational city and economic center in the Banyumas Residency area, has great potential for the development of the halal food industry. The halal food sector has become a primary focus due to the continued growth of the global halal market and Indonesian public awareness of the importance of halal food consumption. This study used a qualitative approach with a case study design to gain a comprehensive understanding of the phenomenon of halal food MSME development. The data collection method involved in-depth interviews with 15 halal food MSMEs selected purposively based on certain criteria such as business duration, product type, and operational scale. Field observations were conducted to observe daily operational practices, while a documentary study analyzed relevant documents such as business permits, halal certificates, and financial reports. The research identified three main challenges facing halal food MSMEs in Purwokerto. First, the complexity of the halal certification process, which involves high costs and complicated administrative procedures. Second, limited access to capital from formal financial institutions, which hinders business expansion. Third, low adoption of digital technology for marketing, which results in limited market reach. However, the research also identified significant opportunities in the form of increased consumer awareness of halal products and the local government's commitment to supporting the development of the sharia economy. Recommended development strategies include improving product quality through standardization, menu diversification to expand the target market, and optimizing the use of digital platforms to increase the visibility and accessibility of halal food products in Purwokerto.